Math Problems

Factor each quadratic equation

## Questions

 $$y = x^2 -x -20$$ $$y = 3 x^2 -5 x + 2$$ $$y = x^2 -2 x -8$$ $$y = 2 x^2 + x -6$$ $$y = 4 x^2 + 15 x + 9$$ $$y = x^2 -1$$ $$y = x^2 + x -2$$ $$y = 4 x^2 -x -3$$ $$y = 4 x^2 + 3 x$$ $$y = x^2 + 12 x + 36$$ $$y = 2 x^2 + 3 x -2$$ $$y = 2 x^2 -4 x -6$$ $$y = 4 x^2 + 13 x + 3$$ $$y = 2 x^2 + 4 x -6$$ $$y = x^2 + 2 x -24$$ $$y = x^2 -x -20$$ $$y = 4 x^2 + 10 x -6$$ $$y = x^2 + 6 x + 5$$ $$y = 3 x^2 + 11 x + 6$$ $$y = x^2 + 2 x -15$$ $$y = x^2 -4 x -12$$ $$y = x^2 -6 x + 5$$ $$y = x^2 + 2 x -8$$ $$y = x^2 -3 x -4$$ $$y = x^2 -8 x + 15$$ $$y = 2 x^2 + 6 x$$ $$y = x^2 -8 x + 12$$ $$y = 2 x^2 -x$$

 $$y = x^2 -x -20$$ ⇒ $$(x + 4)(x -5)$$ $$y = 3 x^2 -5 x + 2$$ ⇒ $$(3 x -2)(x -1)$$ $$y = x^2 -2 x -8$$ ⇒ $$(x -4)(x + 2)$$ $$y = 2 x^2 + x -6$$ ⇒ $$(2 x -3)(x + 2)$$ $$y = 4 x^2 + 15 x + 9$$ ⇒ $$(4 x + 3)(x + 3)$$ $$y = x^2 -1$$ ⇒ $$(x + 1)(x -1)$$ $$y = x^2 + x -2$$ ⇒ $$(x + 2)(x -1)$$ $$y = 4 x^2 -x -3$$ ⇒ $$(4 x + 3)(x -1)$$ $$y = 4 x^2 + 3 x$$ ⇒ $$(4 x + 3)(x)$$ $$y = x^2 + 12 x + 36$$ ⇒ $$(x + 6)(x + 6)$$ $$y = 2 x^2 + 3 x -2$$ ⇒ $$(2 x -1)(x + 2)$$ $$y = 2 x^2 -4 x -6$$ ⇒ $$2(x + 1)(x -3)$$ $$y = 4 x^2 + 13 x + 3$$ ⇒ $$(4 x + 1)(x + 3)$$ $$y = 2 x^2 + 4 x -6$$ ⇒ $$2(x -1)(x + 3)$$ $$y = x^2 + 2 x -24$$ ⇒ $$(x + 6)(x -4)$$ $$y = x^2 -x -20$$ ⇒ $$(x -5)(x + 4)$$ $$y = 4 x^2 + 10 x -6$$ ⇒ $$2(2 x -1)(x + 3)$$ $$y = x^2 + 6 x + 5$$ ⇒ $$(x + 5)(x + 1)$$ $$y = 3 x^2 + 11 x + 6$$ ⇒ $$(3 x + 2)(x + 3)$$ $$y = x^2 + 2 x -15$$ ⇒ $$(x -3)(x + 5)$$ $$y = x^2 -4 x -12$$ ⇒ $$(x + 2)(x -6)$$ $$y = x^2 -6 x + 5$$ ⇒ $$(x -1)(x -5)$$ $$y = x^2 + 2 x -8$$ ⇒ $$(x + 4)(x -2)$$ $$y = x^2 -3 x -4$$ ⇒ $$(x -4)(x + 1)$$ $$y = x^2 -8 x + 15$$ ⇒ $$(x -3)(x -5)$$ $$y = 2 x^2 + 6 x$$ ⇒ $$2(x)(x + 3)$$ $$y = x^2 -8 x + 12$$ ⇒ $$(x -6)(x -2)$$ $$y = 2 x^2 -x$$ ⇒ $$(2 x -1)(x)$$